Wireless Home Networking troubleshoot guidance courseware / Nina Aima Abdullah @ Baharum - Abdullah @ Baharum, Nina Aima (2012)
Home networking is a part of Local Area Network (LAN) that been used for communication purposes whether to the internet and other devices such as printer, scanner and mobile devices. With the growing usage of this network, the problems regarding this network also increasing at the same time. However, the knowledge about the problems and the solutions to the problem is still unknown to the user of wireless home network. Thus, Wireless Home Networking Troubleshoot Guidance Courseware 1st developed significantly to give the wireless home network user the information about network m general, the step by step guidance to solve the problems regarding wireless home network and the definition of related terms in network. The development of this courseware has been designed according to ADDI E Model. A DDIE Model consists of five steps which are analysis, design, development, implementation and evaluation phases. The uses of multimedia courseware can be developed as an interactive learning med i um to give infonnation and knowledge to the users. The evaluation of this courseware is based on Davis Technology Acceptance Model that is focused on perceived of usefulness and perceived ease of use from the user of the courseware.